Review of Educational Philosophy on Islamic Religious Education Curriculum in Indonesia - Bunga Pariama Br Sembiring; Juliani; Meisya Fatiha Andrianti; Salsabila Balqis; Veryna Zahra Alrandy (Journal of Contemporary Gender and Child Studies, 2024)
This study aims to examine the Islamic Religious Education (PAI) curriculum in Indonesia from the perspective of educational philosophy. The focus of this research is to analyze the philosophical foundations underlying the formulation of the PAI curriculum and its relevance to students' needs in facing modern challenges. This research employs a descriptive qualitative method with a document analysis approach to review current PAI curriculum policies. The findings reveal that the PAI curriculum in Indonesia is based on philosophical principles oriented toward Islamic and humanisticvalues. However, challenges arise in its implementation, particularly regarding the integration of religious values with 21st-century skills requirements. This study recommends developing a more adaptive and contextual curriculum without neglecting spiritual and moral aspects.